Studying the workforce in the professional qualification context: the US experience - Perkhun L. Р. (Statistics of Ukraine, 2017)
The article examines the American experience of studying the workforce in the professional context. Statistical analysis of employment by occupation will reveal both trends in change in typical tasks of individual workplaces and objective knowledge, skills and competencies of workers in different sectors of the economy and the risks of their inconsistency with formal qualifications. The results of statistical analysis of employment by occupation can be used to elaborate and adjust strategies for the development of the economy of the state or its individual sectors (for the development of the economy at federal, state and industry level), educational institutions, to choose a future profession, to determine career development tools, and to choose the business location Comparative analysis of the contents of the normative documents on the classification of professions of the United States and Ukraine showed the need to develop a new version of the normative document for the classification of occupations in the professional context on the basis of the existing Classifier of professions and the Directory of Qualification Characteristics. The results of the statistical study of the workforce in terms of professions are displayed on the official BLS. However, more interesting and useful for a common user is a specially created OnLine 0*NET service. On request for the chosen profession, the complete information (“summary”) is provided: the title and the code of the profession, the nomenclature of professional tasks, the sample of reported job titles, the nomenclature of typical tasks of the activity, the necessary knowledge, professional skills, technology skills, abilities; work activities; the description of the work context, the required level of education; educational institutions and certification centers where you can get training or further training in the chosen profession; necessary personal qualities; related occupations; wages & employment trends (for each State and each type of industries); job openings on the web. There is no similar service in Ukraine. In order to create an effective system for studying the workforce in Ukraine professionally and to use convenient services for the results obtained, the efforts of scientists, practitioners and IT specialists need to be combined.